Functional characterization of transcription factor WIN1 genes associated with lipid biosynthesis and stress tolerance in soybean (Glycine max) - Cai, Guiping; Liu, Baoling; Zhou, Yali; Gao, Huiling; Xue, Jinai; Ji, Chunli; Zhang, Li; Jia, Xiaoyun; Li, Runzhi (Environmental and experimental botany, 2022)
Transcription factor WAX INDUCER1 (WIN1) plays an important role in wax and cutin biosynthesis in plants. In this study, six GmWIN1 genes were identified from soybean (Glycine max), with GmWIN1–5 having high expression in flowers and seeds, particularly under cold stress. GmWIN1–5′s functions in lipid/oil biosynthesis and stress tolerance were characterized by its overexpression in soybean hairy roots and tobacco (Nicotiana benthamiana) plants. Under cold stress, GmWIN1–5 overexpression (GmWIN1–5-OE) resulted in large oil enhancement and high level of phospholipids involved in cell membranes formation. Malondialdehyde content and elcetronlyte leakage in GmWIN1–5-OE plants was smaller than that in the wild-type control under cold stress, indicating that GmWIN1–5 promote plant stress tolerance. Moreover, GmWIN1–5-OE also led to upregulated expression of numerous genes involved in de novo fatty acid biosynthesis and triacylglycerol (TAG) production, including genes encoding phospholipase D (PLD), biotin carboxyl carrier protein 1 (BCCP1), lysophosphatidic acid acyltransferase 5 (LPAT5), and diacylglycerol acyltransferase 2 (DGAT2). GmWIN1–5 directly bound to the promoter region of PLD gene. Overall, the results revealed that GmWIN1–5 can upregulate the biosynthesis and accumulation of lipids/oils, especially unsaturated fatty acids and phospholipids benefiting membrane integrity, and ultimately confer plants with high stress tolerance. •Six GmWIN1 members with structural integrity are identified in soybean (Glycine max).•Of the six GmWIN1s, GmWIN1-5 expression level was the highest in flower and seed tissues.•Overexpression of GmWiN1-5 in soybean hair roots increased total lipids and cold stress tolerance.•Ectopic expression of GmWIN1-5 in tobacco plant boosted oil content and stress tolerance.•GmWIN1-5 promoted expression of several lipid synthesis-related genes, particularly PLD.